Peningkatan Pengetahuan Promosi Berbasis Digital pada Perusahaan Clothing Dobujack Kota Bandung - Supriyanto, Dodi; Basuki, Teguh Iman (Universitas Ekuitas Indonesia, 2023)
Dobujack is a small home industry business engaged in the distribution of clothing (confection) located at Jalan Purwakarta No. 147, Antapani District, Bandung City. The main problem faced by Dobujack is increasing sales through attractive promotions, packaging, and online digital marketing promotions. To overcome these problems, the solutions offered are assistance in making packaging designs, increasing knowledge about digital-based promotions, and making attractive packaging designs. Activities in this community service are divided into several months: the first month is a preliminary survey, the second is a discussion of mentoring, the third is training, the fourth is mentoring, and the fifth is preparing a service report. The target to be achieved is that partners can understand and create attractive packaging to upload on social media. Keywords: Packaging, Promotion knowledge ABSTRAK Dobujack merupakan usaha industri kecil rumahan yang bergerak di bidang distribusi pakaian (konfeksi) yang berlokasi di Jalan Purwakarta No. 147, Kecamatan Antapani, Kota Bandung. Masalah utama yang dihadapi Dobujack adalah meningkatkan penjualan melalui promosi yang menarik, kemasan, dan promosi pemasaran digital online. Untuk mengatasi permasalahan tersebut, solusi yang ditawarkan adalah pendampingan pembuatan desain kemasan, peningkatan pengetahuan tentang promosi berbasis digital, dan pembuatan desain kemasan yang menarik. Kegiatan pengabdian kepada masyarakat ini dibagi menjadi beberapa bulan yaitu bulan pertama survei pendahuluan, bulan kedua diskusi pendampingan, ketiga pelatihan, keempat pendampingan, dan kelima pembuatan laporan pengabdian. Target yang ingin dicapai adalah mitra dapat memahami dan membuat kemasan yang menarik untuk diunggah di media sosial. Kata kunci: Kemasan, Pengetahuan promosi